INSTRUCTIONAL DESIGN OF READING MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL IN LUBUKLINGGAU - Maria Ramasari; Agus Triyogo; Ardayati Ardayati (Universitas Sarjanawiyata Tamansiswa, 2019)
The aim of this research is to develop the English reading materials in textbook used for students at Senior High School in Lubuklinggau, and to describe the efficacy of instructional design of reading materials for Students at Senior High School in Lubuklinggau. The Eleventh Grade Students of SMA Negeri 5 Lubuklinggau was the sample of this research. In addition, this research applied an Educational Research and Development (R & D) by using a simplified six steps of Borg and Gall’s model. The six steps were: (1) collecting the research information,(2) planning and drafting the data of research, (3) developing the data of research based 2013 curriculum combined with the result, (4) giving tryout (field testing) to the 11th grade students of SMA Negeri 5 Lubuklinggau, (5) evaluating the English reading materials by the experts, and (6) producing the final product (English reading materials in textbook). The findings of this research showed that the English reading materials in textbook that were developed in this research fulfilled the criteria of R & D model. The instructional design as the specific English reading materials was very important and useful to support the students’ reading activities that put not only building the intensive practice for reading comprehension, but also linking to grammar, enriching the vocabulary, and applying the students’ knowledge. Moreover, through the English reading materials in textbook, the students could use it with the suitable and the valuable materials, and they must be motivated to increase their reading proficiency.